Larva of Palaemnema brasiliensis Machado (Odonata: Platystictidae), from Amazonas, Brazil - Neiss, Ulisses Gaspar; Hamada, Neusa (Zootaxa, 2016)
The larva of Palaemnema brasiliensis Machado, 2009 is described and illustrated based on last-instar larvae and exuviae of reared larvae collected in a blackwater stream in Barcelos and Presidente Figueiredo municipalities, Amazonas state, Brazil. The larva of P. brasiliensis can be distinguished from the two South American species of the genus with described larvae (P. clementia Selys and P. mutans Calvert), mainly by presence of a single obtuse cusp on the labial palp, the presence and configuration of setae in the caudal lamellae, and the proportional length of terminal filaments of the caudal lamellae. The family is recorded here for the first time in Brazilian state of Amazonas.